Perubahan Paradigma Pemolisian di Era Pandemi Covid-19 - Condro, Susatyo Purnomo (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
This article aims to provide an analysis of modern policing models in the emergency situation of the Covid-19 pandemic. The method used in this study is in the form of literature review, and secondary data. The results of the study shows that policing models such as democratic policing and community policing is not effective and fast enough as a strategy for responding to the COVID-19 pandemic emergency situation. In an emergency situation, a policing intervention model is needed that emphasizes a combination model between values and norms-based settings in the community with regulations based on the legitimacy of the police authority. Policing intervention from the community side is directed at changing the mindset of the community from being defensive towards COVID-19 to an open understanding of the existence and spread of COVID-19.